The Reform of Research Ethics Committees in Italy: Challenges and Perspectives (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The paper offers a critical analysis of the current configuration of research ethics committees in Italy, in light of Regulation (EU) No. 536/2014 and the recent establishment of the Territorial Ethics Committees (CET). After retracing the origins and functions of these committees, it discusses the main critical issues that have emerged during the first years of CET activity. The paper proposes to reinterpret the role of ethics committees as spaces for moral reflection and the promotion of research ethics, emphasizing the importance of maintaining coherence with their authentic ethical mission.
Keywords: research ethics; research ethics committees; Regulation (EU) No 536/2014; Italian ethics committees; clinical research